PROCEDURE FOR PROTECTION AGAINST WORKPLACE HARASSMENT AT THE EMPLOYER LEVEL IN DOMESTIC LAW - Adžić, Stevan (Glasnik Advokatske komore Vojvodine, 2025)
This paper analyzes the effectiveness of mechanisms for workplace harassment protection in Serbia, with the aim of improving the legal and organizational framework. The research focuses on mediation processes as an alternative dispute resolution method that can contribute to more efficient and fair treatment of employees. Special attention is given to internal procedures that employers can implement to combat harassment and protect their employees. The paper also considers how successful resolution of these issues can positively impact the work environment, creating a healthier and more productive atmosphere. Through this analysis, concrete guidelines are provided for enhancing worker protection and promoting overall well-being in the workplace. With this research question, the paper addresses a significant topic that requires a comprehensive approach, including legislative, organizational, and social aspects.
Keywords: Workplace dispute resolution; workplace harassment; mediation; negotiation